A model for establishing and developing relationships with visitors of the Kopački rit Nature Park based on mobile technologies (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2015)
Kopački rit as a nature park is a great tourist attractor in northeastern Croatia. Its flora and fauna used to attract people for economic reasons, whereas today people mostly visit it for educational and tourism purposes. Visitor loyalty is increasingly important in tourism development today. One-time visitors cannot be the basis of tourist demand. Such guests often visit a particular destination motivated by global political trends, and not by the need to visit the destination itself. For example, the increased number of guests in Croatia in the past few years is a result of political events in Greece and North Africa. Once the political situation in their primary choice is stabilised, such guests will be lost. Therefore, among many guests of Kopački rit one must recognise those, for whom it was their primary destination, and establish a relationship with them. To achieve a targeted tourist offer, the Nature Park must implement relationship marketing by means of Customer Relationship Management (CRM). The aim of this research is to explore and define an optimum model of the CRM system that would offer a long-term solution to the problem of customer relationship development with visitors to Kopački rit. The research will be carried out deductively, and the methods used to realize the research aim are to be systematic analysis, causal reasoning, descriptive modelling, and logical experiment. The result is a framework model of a marketing database and a descriptive conceptual model of the CRM system for Kopački rit, both of which will use the potentials of mobile and information and communication technologies.